Practice Patterns Among Korean Urologists for Glans Penis Augmentation Using Hyaluronic Acid Filler in the Management of Premature Ejaculation - Jeong, Hyeong Guk; Ahn, Sun Tae; Kim, Jong Wook; Seo, Kyung Keun; Lee, Dong Soo; Uh, Hong Sun; Kim, Je Jong; Moon, Du Geon (Sexual medicine, 2018)
Glans penis augmentation (GPA) using hyaluronic acid (HA) gel has been developed for treating premature ejaculation (PE) with penile hypersensitivity. The injected HA filler creates a barrier that reduces the tactile stimuli to the hypersensitive dorsal nerve. Although the HA filler is biodegradable and is believed to not cause permanent loss of sexual function, the current International Society for Sexual Medicine guideline for PE does not recommend this procedure owing to concerns regarding sexual dysfunction. To investigate the practice patterns for GPA using HA filler among Korean urologists, and to identify whether urologist experienced patient reports of sexual dysfunction post-treatment. Between March 2016 and July 2016, a specially designed questionnaire was mailed to 86 selected Korean urologists who had used injectable materials to treat PE. The prevalence and awareness of sexual dysfunction after GPA using HA filler were evaluated. Overall, 56 urologists completed the survey (response rate: 69.2%), of which 36 (64.3%) had performed GPA using HA filler. They reported having performed a combined total of 4,344 such GPA procedures. Most urologists (72.7%) performed GPA using HA filler in patients who benefit from topical anesthetics. Patients with a history of failed pharmacotherapy (59.1%) and selective dorsal nerve neurotomy (45.5%) were selected for GPA using HA filler. The respondents (44.4%) encountered overall 206 (4.7%) cases of patients reports of recurrence of PE. Interestingly, only 36 (0.8%) cases of glans pain or paresthesia and no cases of erectile dysfunction post-treatment were reported. Korean urologists performed GPA using HA filler when pharmacotherapy failed or if there was a response to topical treatment. Paresthesia and hypoesthesia after GPA using HA filler are rare, and no cases of erectile dysfunction were encountered by Korean urologists. Jeong HG, Ahn ST, Kim JW, et al. Practice Patterns Among Korean Urologists for Glans Penis Augmentation Using Hyaluronic Acid Filler in the Management of Premature Ejaculation. Sex Med 2018;6:297–301.